Lower eyelid excursion: A functional and cosmetically relevant parameter in the treatment of lower eyelid retraction. Issue 2 (February 2019) - Beigi, B.; Khandwala, M.; Degoumois, A.; Ogbuehi, K.C.; Gupta, D.
Summary: The purpose of this study was to assess and quantify lower lid excursion following repair of lower lid retraction. In this retrospective cohort study, a case review of patients who had undergone ear cartilage grafting for lower lid retraction was undertaken. Surgical correction involved the placement of autologous cartilage between the tarsal plate and lower lid retractors. Measurements taken preoperatively and postoperatively were the marginal reflex 2 (MRD2) and the lower scleral show (LSS). The lower lid excursion on downgaze (LLE) was measured only postoperatively with a comparison made between operated eyes and control eyes. Thirteen eyelids of 10 patients were included in the study. Preoperatively, MRD-2 ranged from 4 to 8 mm (6.5 ± 1.5 mm) – mean ± SD. Postoperatively, MRD-2 ranged from 4 to 6 mm (5.1 ± 0.7 mm). The difference in mean MRD2 was statistically significant ( p < 0.05 ). Preoperatively, LSS ranged from 0 to 5 mm (2.5 ± 1.6 mm). Postoperatively, LSS ranged from 0–1 mm (0.1 ± 0.3 mm). The difference in mean LSS was statistically significant ( p < 0.01). Postoperatively, all lower eyelids achieved movement on downgaze. On the operated eyes, the eyelid excursion ranged from 2 to 5 mm (3.1 ± 1.0 mm) on downgaze. On the nonoperated (control) eyes (where the operations were not performed bilaterally), the eyelid excursion ranged from 1 to 4 mm (2.8 ± 1.2 mm). There was no statistically significant difference in the lid excursion of operated and nonoperated eyes ( p > 0.05 ). It is possible to correct lower lid retraction in both primary and secondary positions of gaze if an appropriate surgical technique is employed.